Molecular magnetic properties of a dysprosium(III) complex coordinated to a nonadentate bispidine ligand - Cieslik, Patrick; Comba, Peter; Hergett, Waldemar; Klingeler, Rüdiger; Plny, Günter Finn Peter; Spillecke, Lena; Velmurugan, Gunasekaran (Zeitschrift für anorganische und allgemeine Chemie, 2021)
The DyIII complex of the nonadentate bispidine L1 (bispidine=3,7-diazabicyclo[3.3.1]nonane) has a capped square antiprismatic structure, known to lead to suppressed quantum relaxation of magnetization by quantum tunneling. [DyIIIL1]OTf indeed is an SMM with a modest barrier to magnetization relaxation. The experimentally determined barrier of 46 cm−1 is confirmed by ab initio calculations (43.5 cm−1), and the quantum-chemical analysis indicates that ligand modifications, leading to a higher symmetry and a stronger axial ligand field should significantly increase the effective barrier to magnetization relaxation.